Alternatives to substitute and reduce the use of mercury in artisanal mining in Madre de Dios - Torre Ureta, Paola Angela (2022)
There are high concentrations of vaporized mercury beyond what is permissible in areas of the department of Madre de Dios, product of gold mining, it is estimated that this department produces 70% of the gold from artisanal mining in the country, which are covered by the Law No. 27651 Law for the Formalization and Promotion of Small-scale Mining and Artisanal Mining and its Regulations Supreme Decree No. 013-2002-EM; but that cause environmental problems and health problems for artisanal miners who use it for amalgamation and obtaining gold. With the objective of reviewing, summarizing, and analyzing the available information on substitution alternatives and reduction of the use of mercury (Hg) in artisanal mining; it was shown that there are methods that include more effective ways of concentrating gold; for this, devices are used to capture mercury, or the use of processes that replace it. Its viability being subject to conditions in the area, specialized advice, a good environmental management system and optimization guidelines.